The Effect of Farming Systems and Cultivars on the Qualitative and Quantitative Composition of Bioactive Compounds in Winter Wheat (Triticum aestivum L.) - Iwona Kowalska; Agata Soluch; Jarosław Mołdoch; Krzysztof Jończyk (Molecules)
Triticum aestivum L. subsp. spelta (cv. Rokosz) and common winter wheat Triticum aestivum L. subsp. aestivum (cv. Arktis, Belissa, Estivus, Fidelius, Hondia, Jantarka, KWS Ozon, Linus, Markiza, Ostka Strzelecka, Pokusa) grown in an organic farming system were analyzed and compared. Furthermore, the productivity of four common wheat cultivars (cv. Fidelius, Hondia, Jantarka, KWS Ozon) grown under four different (organic, conventional integrated, and monoculture) farming systems was compared. Using UPLC-DAD-MS, UPLC-PDA-MS/MS, and TLC-DPPH•, nine phenolic acids, nine alkylresorcinols, and their antiradical activity were identified and quantified. In the organic farming system, the highest yield was observed for T. aestivum L. subsp. aestivum cv. Fidelius (4.17 t/ha). Infections of wheat cultivars were low or at a medium level. The highest resistance to Fusarium fungi was shown by cv. Fidelius, which also exhibited the highest alkylresorcinol content and antioxidant capacity. The total phenolic acid content was highest in cv. Rokosz (1302.3 µg/g), followed by common winter wheat cultivars cv. Linus (1135.1 µg/g) and cv. Markiza (1089.6 µg/g). The potential of winter wheat cultivars for human health and their suitability for cultivation in different production systems was determined, showing significant differences in bioactive compounds depending on cultivars, systems, and years.